Dataset on leaching properties of coal ashes from Malaysian coal power plant - Beddu S.; Abd Manan T.S.B.; Zainoodin M.M.; Khan T.; Wan Mohtar W.H.M.; Nurika O.; Jusoh H.; Yavari S.; Kamal N.L.M.; Ghanim A.A.; Pati S.; Abdullah M.T. (Elsevier Inc., 2023)
Coal combustion by-products (CCPs) (i.e. fly (FA) and bottom (BA) ashes) generated by power plants contain heavy metals. This research presents leaching properties of coal ashes (FA and BA) collected from Jimah coal-fired power station, Port Dickson, Negeri Sembilan using USEPA standard methods namely toxicity characteristic leaching procedure (TCLP), and synthetic precipitation leaching procedure (SPLP). Heavy metals like lead (Pb), zinc (Zn), copper (Cu) and arsenic (As) were quantified using atomic absorption spectrometer (AAS). The leached of heavy metals fluxes were Cu < Zn < Pb < As. As leached the most whilst indicating of possible contamination from As. Overall, the ranges of leached concentration were adhered to permissible limits of hazardous waste criteria for metal (Pb and As) and industrial effluent (Zn and Cu). The presented data has potential reuse as reference for the coal ash concrete mixed design application in construction industries. 2020 The Author(s)